PENGARUH PEMBERIAN EKSTRAK BIJI JINTEN HITAM (Nigella sativa) TERHADAP KADAR GSH, MDA, JUMLAH SERTA FUNGSI SEL MAKROFAG ALVEOLAR PARU TIKUS WISTAR YANG DIPAPAR ASAP ROKOK KRONIS - Marwan, Marwan; Widjajanto, Edi; Karyono, Setyawati (Jurnal Kedokteran Brawijaya, 2005)
Cigarette smoke is the main risk factor of chronic  obstructive pulmonary disease (COPD). Several studies about COPD has focused on the oxidative stress in lung. Oxidative stress was related to inactivation of antiprotease enzymes, airway epithelial destruction and proinflammatory genes expression. Antioxidant may useful for treatment of COPD. Black seed (Nigela sativa) studies have showed that black seedhas antioxidant activity. The aim of this research  was to prove that black seed crude extract can protect wistar rat lung from oxidative stress which was caused by chroniccigarette smoke exposure. This experimental research used randomizedcomplete design with control group. Thirty wistar strain of Rattus novergicus, 2.5 to 3 months old, 150 – 250 grams ofweight were divided into five groups. First group  was used as negative control group (without any treatment), second group as positive control group (only cigarettesmoke exposure treatment), third group as cigarette smoke exposureand black seed crude extract dose 0.6 gr/kilogram  of body weight/day (group A), cigarette smoke exposure and  black seed crude extract dose 1.2 gr/kilogram of body weight/day (group B) and cigarette smoke exposure and black seed crude extract dose 2.4 gr/kilogram of body weight/day (group C). After 3 months five parameters were measured in this research.